The bioactivity profile of Ixora chinensis ("santan-tsina") leaves toxicity, antioxidant and antimicrobial activities - Uy, Mylene M. (Asia-Pacific Journal of Science, Mathematics, and Engineering, 2015)
This work investigated the bioactivites of the hexane (IcH), chloroform (IcC) and aqueous (IcA) fractions obtained by sequential partitioning of the ethanolic leaf extract of the plant Ixora chinensis. The fractions were evaluated for toxicity using the brine shrimp lethality test (BLST) against artemia salina leach; for antioxidant property using the DPPH- radical scavenging test, total antioxidant activity by phosphomolybdenum method and total phenolics content by Folin-Ciocalteu method and for antimicrobial activities using paper disc diffusion method. In the toxicity test, only the IcH fraction showed activity. In the antioxidant activity screening, all fractions exhibited low antiradical activities, fraction IcC showed the relative highest total antioxidant potential and fraction IcH demonstrated the highest total phenolics content. In the antimicrobial assay, IcC was active against A. niger and partially active towards B.subtilis while IcH was inactive against all the test microorganisms.